Finance and Development, December 1994. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1994)
THE SOVIET experience teaches at least one cautionary lesson: development strategies emphasizing state-administered investment may produce rapid growth at first but are prone to eventual stagnation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet